2014
DOI: 10.1007/s00404-014-3418-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical exercise on postpartum fitness, hormone and lipid levels: a randomized controlled trial in primiparous, lactating women

Abstract: Implementation of a low-impact exercise training program appears to improve physical fitness of postpartum women, while it does not seem to affect lipid levels and lactation-associated hormone levels. Hence, implementation of an exercise training program combining low-impact dance aerobic, resistance and stretching exercise is feasible in postpartum, primiparous, lactating women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…Eleven studies provided a named theory for the intervention, mostly social cognitive theory (n = 8) and transtheoretical model (n = 2) . Several others provided a rationale for the intervention without articulating the theory used (n = 4) . The remainder did not describe the rationale for the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies provided a named theory for the intervention, mostly social cognitive theory (n = 8) and transtheoretical model (n = 2) . Several others provided a rationale for the intervention without articulating the theory used (n = 4) . The remainder did not describe the rationale for the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were conducted on premenopausal eumenorrheic women [ 22 32 ], one study on perimenopausal women [ 33 ], 13 studies on postmenopausal women [ 21 , 34 53 ], and 12 studies on women with polycystic ovary syndrome (PCOS) [ 54 – 67 ]. One study did not specify the hormonal status of participants [ 68 ], and one study was conducted on perpartum women [ 69 ] and two studies on postpartum women [ 70 , 71 ]. The mean age of participants varied between 15.5 and 71.0 years; the mean BMI varied between 19.9 and 39.0 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with a study by Zourdalani (2015) that found the implementation of low-intensity physical exercise programs seems to improve physical and overall fitness in postpartum women, including increased cardio-respiratory function, muscle strength, and endurance of the upper and abdominal limbs, stretching the musculoskeletal back and thighs, and a reduction in total body fat. Physiologically, muscle resistance is known to decrease after childbirth along with hormonal changes that occur (19)(20). With the presence of physical exercise, especially yoga can improve muscle strength, stretching, and relaxation so that the quality of postpartum life is increased (21)(22).…”
Section: Discussionmentioning
confidence: 99%